Efektivitas Lean Logistik Pada Pengelolaan Stok Barang Pada Studi Kasus UMKM “Hoslindshop’’ - Ankita, Syahla Nasywa; Akbardin, Juang; Wulansari, Dwi Novi (Jurnal Industri dan Teknologi Samawa, 2025)
Hoslindshop, a micro, small, and medium enterprise engaged in selling Muslim clothing, faces issues of overstock and product defects due to ineffective inventory management. This study aims to identify existing waste and analyze suitable lean logistics strategies to improve operational efficiency. A qualitative approach was used, involving literature review and documentation analysis, supported by the application of PDCA, 5S, and Lean Six Sigma (DMAIC) methods. The results revealed three main types of waste: waiting, inventory, and defects. Lean strategies such as kaizen, Just-In-Time inventory management, and digital inventory systems effectively increased efficiency, reduced waste, and maintained product quality. The study concludes that lean logistics implementation provides significant benefits in enhancing operational efficiency, lowering costs, and improving customer satisfaction in Hoslindshop’s operations